Cryoresistance of Human Embryos at the Morula Stage with Aberrant Compaction - Yurchuk, Taisiia A.; Petrushko, Marina P.; Pinyaev, Volodymyr I. (Problems of Cryobiology and Cryomedicine, 2017)
Probl Cryobiol Cryomed 2017; 27(2):169.